Inverse magnetic catalysis in nonlocal chiral quark models - Pagura, Valeria Paula (2018)
We study the behavior of strongly interacting matter under an external magnetic field in the context of nonlocal Polyakov-Nambu-Jona-Lasinio (PNJL) -like models. We find that at zero temperature the condensates display the well-known Magnetic Catalysis effect, showing a good quantitative agreement with lattice QCD results. Moreover, when extended to finite temperature we find that the Inverse Magnetic Catalysis effect is naturally incorporated.